The development of legal education in classical universities of Ukraine in 1991-2002 - Denys Skorodumov (Cхід, 2013)
The development process of the Ukrainian society which has been taking place during first eleven years of its existence, promoted demand for specialists in the sphere of right. Cardinal renovation of a state system in 1991 created conditions for reorganization of the training system of specialists in this sphere. Practical steps in granting the higher legal education were taken by classical universities. The development of legal education inUkrainecan be divided into in three stages. The first stage (1991-1996) - specialists were trained at seven classical universities. During this period there were changes connected with the process of jurists and lawyers preparation. The second stage (1996-2001) - acceptance in 1996 of the Constitution ofUkraineobliged all social and state institutes to implement all statutory provisions. Competent specialists of the sphere of right were necessary for this purpose. For this reason the social demand for lawyers boosted, and the offer in their preparation increased as well. The number of the classical universities providing the higher legal education increased to thirteen. The third stage (2001-2002) - the changes directed towards the improvement of granting legal education continued. It allowed classical universities to provide  many-sided legal education in "Jurisprudence" and to teach the students concrete legal professions that further gave them advantages in employment and their future career development. After high school graduation graduates received either qualification "lawyer", or "jurist".